ANALISIS KEMAMPUAN GURU PAUD DALAM MEMBUAT MEDIA PEMBELAJARAN DI KECAMATAN JARAI KABUPATEN LAHAT SUMATERA SELATAN - Febey Harsela; Didik Suryadi (Al Fitrah: Journal Of Early Childhood Islamic Education, 2021)
This type of research used in this research is quantitative research with survey methods and questionnaire data collection techniques (questionnaires) in this study using data sources namely the head of the PAUD school in Jarai District, Lahat Regency, South Sumatra. From the research conducted by researchers, it can be concluded that the ability of PAUD teachers in making learning media in Jarai Subdistrict, Lahat Regency, South Sumatra is included in strong categories or well-called. Most of the PAUD teachers in Jarai Subdistrict, Lahat Regency have been able to make learning media according to the criteria and categories that are stipulated, although there are still some who have not been able to. However, unfortunately in-depth knowledge about the importance and necessity of learning media in the learning process is still lacking, many PAUD teachers do not use instructional media on the grounds that it is not really needed as long as children are taught